As aves limícolas migratórias nas praias de Aracaju : avaliação da influência antrópica e contribuição para ações de desenvolvimento costeiro - Almeida, Bruno Jackson Melo de (2010)
The incessant growth of human populations, and the increase in recreational activities on seashores have altered the natural conditions of most coastal ecosystems, with a series of consequences for the distribution, abundance, and behavior of a range of organisms. While Atalaia beach in the city of Aracaju is highly urbanized, it is an important point in the migratory cycle of some species of migratory Nearctic shorebirds. The principal objective of the present study was to characterize the avian fauna of Atalaia beach, and to evaluate the influence of anthropogenic impacts on the spatial distribution and habitat use of migratory shorebirds. For this, a total of 81 surveys of a 5 km stretch of the beach were conducted on a monthly basis between October, 2008, and November, 2009. Data were also collected on the homogeneous availability organic matter of benthic macrofauna and the presence of beachgoers along the same stretch of shore. A total of 70 bird species were identified, of which the most abundant were the migratory shorebirds, with over 2500 individuals being recorded between October and March. The most common species were Arenaria interpres, Calidris alba, Calidris pusilla, and Charadrius semipalmatus, which together accounted for 79,09% of all birds recorded. These species were not distributed homogeneously across the survey area (H = 31.98; g.l. = 9; p = 0.002), nor did their abundance correlate with the availability of invertebrates (rs = 0.14; p = 0.71; n = 10). Unexpectedly, the sectors of the area with the highest concentrations of beachgoers also harbored the greatest abundance of birds (rs = 0.61; p = 0.059; n = 10). This appears to have been at least partly explained by the availability of leftover food within these areas, which represent an alternative dietary resource for the migratory shorebirds, and interferes in their behavior patterns. There is a clear need to better understand this phenomenon, and its potential consequences for the birds.